2021
DOI: 10.1093/bib/bbab356
|View full text |Cite
|
Sign up to set email alerts
|

A cross-study analysis of drug response prediction in cancer cell lines

Abstract: To enable personalized cancer treatment, machine learning models have been developed to predict drug response as a function of tumor and drug features. However, most algorithm development efforts have relied on cross-validation within a single study to assess model accuracy. While an essential first step, cross-validation within a biological data set typically provides an overly optimistic estimate of the prediction performance on independent test sets. To provide a more rigorous assessment of model generaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 64 publications
1
51
0
Order By: Relevance
“…In addition, the models were validated with data from within the same drug combination screening study. Although this is a common model evaluation strategy, cross-validation within a single study has been shown to overestimate model generalizability [73]. In the future it would be interesting to assess different DL modeling strategies by performing a cross-study evaluation of the models as well [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the models were validated with data from within the same drug combination screening study. Although this is a common model evaluation strategy, cross-validation within a single study has been shown to overestimate model generalizability [73]. In the future it would be interesting to assess different DL modeling strategies by performing a cross-study evaluation of the models as well [73].…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a common model evaluation strategy, cross-validation within a single study has been shown to overestimate model generalizability [73]. In the future it would be interesting to assess different DL modeling strategies by performing a cross-study evaluation of the models as well [73]. Since ComboScore predictions should be independent of the order of the drugs in a given combination, we considered reverse drug order < cell line, drugB, drugA > triplets to be duplicates and the ComboScores for experiments involving the same cell line and same drug combination were averaged.…”
Section: Pathway Propagation Methods Have Been Employed In Other Drug...mentioning
confidence: 99%
“…The sample size of PDXs is usually orders of magnitude smaller than the analogous CCL datasets. It has been shown that increasing the amount of training samples improves generalization performance of supervised learning models in vision and text applications [17,18], as well as drug response models in CCLs [19,20]. Collecting PDX response data, either through experiments or integration of multiple datasets, carries considerable technical and financial challenges.…”
Section: Introductionmentioning
confidence: 99%
“…UNOMT application is part of CANDLE Wozniak et al (2020), Xia et al (2021) research conducted by Argonne National Laboratory, focusing on automated detection of tumour cells using a deep learning approach. The uniqueness of this approach is the composition of a data engineering workload followed by a deep learning workload written in PyTorch.…”
Section: Introductionmentioning
confidence: 99%